Biology of plagues : evidence from historical populations - Scott, Susan, 1953- (Cambridge University Press, 2001)
Even today, the threat of unstoppable plague is ever-present. Historically, in Europe, the most devastating plagues were between the Black Death and the Great Plague of London. This fascinating book shows that these were not bubonic plague as previously thought, and provides food for thought for social and biological scientists.